Molecular Adjuvants Based on Plasmids Encoding Protein Aggregation Domains Affect Bone Marrow Niche Homeostasis - Sabbieti, Maria G.; Lacava, Giovanna; Amaroli, Andrea; Marchetti, Luigi; Censi, Roberta; Di Martino, Piera; Agas, Dimitrios (Current Gene Therapy, 2017)
Background: During last years, DNA vaccine immunogenicity has been optimized by the employment of co-stimulatory molecules and molecular adjuvants. It has been reported that plasmid (pATRex), encompassing the DNA sequence for the von Willebrand A (vWA/A) domain of the Anthrax Toxin Receptor-1 (ANTXR-1, alias TEM8, Tumor Endothelial Marker 8), acts as strong immune adjuvant by inducing formation of insoluble intracellular aggregates. Markedly, we faced with upsetting findings regarding the safety of pATRex as adjuvant since the aggregosome formation prompted to osteopenia in mice. Objective: The present study provides additional evidences about the proteinaceous adjuvants action within bone marrow and questioned regarding the self-aggregation protein adjuvants immunotoxicity on marrow niches. Methods & Results: Using histological, biochemical and proteomic assays we shed light on pATRex effects within bone marrow niche and specifically we evidenced an aplastic-like bone marrow with disrupted cytokine/chemokine production. Conclusion: The above findings provide compelling support to the thesis that adjuvants based on plasmids encoding protein aggregation domains disrupt the physiological features of the bone marrow elements.
Keywords: Bone marrow niche